The nature and function of the Ernian lüling manuscript unearthed from Zhangjiashan Han tomb no. 247. (7th May 2019) - Jingrong, Li
Abstract: Legal manuscripts excavated from tombs serve as important materials for research on Qin and Han laws. These manuscripts differ from received legal texts or law documents found at archaeological sites in nature and function, as they were stored as funeral texts in tombs. This article studies the Ernian lüling manuscript in terms of its nature and function. It argues that the manuscript compiled in the second year of Empress Lü (186bce ) nearing the death of the owner was not produced for official use but specifically for burial in the tomb. This article further proposes that the burial of the Ernian lüling manuscript may have taken place to illustrate the social status and official capabilities of the owner to the underworld. The investigation of the Ernian lüling manuscript in its archaeological context helps us achieve a stronger understanding of the dating, origins, completeness, and compilation of its text.